EVALUASI PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA PT. PUPUK SRIWIDJAJA PALEMBANG - , Taufiq Akbar, Dr. Agus Setiawan, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The background of this research is based on a Mandatory CSR activities undertaken in the form of Porgram Kemitraan BUMN. BUMN is deemed not capable of running Program Kemitraan, becouse BUMN has different business activities from activities in Program Kemitraan relating to assistance to small businesses in the form of micro credit. The purpose of this study was to determine the attitude of BUMN's management, especially for PT Pupuk Sriwidjaja about CSR rules and to evaluate the steps taken by management in implementing that Mandatory CSR. The data of this study is the primary and secondary data. The primary data was collected from both management PKBL PT Pupuk Sriwidjaja and their trained partners. While the secondary data was obtained from company records and reports of PT Pupuk Sriwidjaja PKBL Management. The results of this study showed an active attitude and proactive management of PT Pupuk Sriwidjaja PKBL in implementing the Program Kemitraan. CSR-run led to CSR Corporate Citizenship. There were many weaknesses of trained partners which should be more emphasized by Management. Therefore, Manajemen needed the internal reporting which not only reported about financial performance but also required reporting of non-financial performance in order to run Program Kemitraan as effective as possible. Constraints in this study was the limited access to data so thus researchers could only do the research in Palembang and investigators did not find data of the trained partners whom have problem in credit payment form both management and review on the field.